Multiple messengers of fast radio bursts. (November 2018) - Burke-Spolaor, Sarah
Multi-wavelength and multi-messenger astronomy will reveal the phenomena that produce fast radio bursts, turning fast radio bursts into sharper tools with which to probe extragalactic plasma.